2020
DOI: 10.1038/s41598-020-69385-1
|View full text |Cite
|
Sign up to set email alerts
|

Survival of forensic trace evidence on improvised explosive devices: perspectives on individualisation

Abstract: Neutralisation of improvised explosive devices. A ballistic water jet was fired onto the suitcases with a RE70 M3 Plus Waterjet Disruptor (Chemring Technology Solutions). This weapon interrupts electrical circuits without recoil by firing an electrically initiated 0.5 caliber cartridge. This cartridge contains a projected waterjet of 150 ml, fired under high pressure. The weapon was oriented 45 • with the longitudinal surface of the suitcase. After each disarmament, fragments were collected and packaged separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…10 In addition, a study by Vanderheyden et al showed that it is possible to recover DNA evidence on submerged improvised explosive devices. 11 Based on the aforementioned information, cellular retention on a substrate and how well the substrate protects deposited cellular material seems to play a role in the quality of DNA recovered from different items.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, a study by Vanderheyden et al showed that it is possible to recover DNA evidence on submerged improvised explosive devices. 11 Based on the aforementioned information, cellular retention on a substrate and how well the substrate protects deposited cellular material seems to play a role in the quality of DNA recovered from different items.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies continue to elucidate the ability to generate DNA profiles from samples taken from touched objects [61][62][63][64]. Additional studies evaluated means of generating human DNA profiles from traces of biological material left on various items, includ-ing hair [65], bricks [66], dogs [67], bite marks in food [68], paper documents [69], eye wear [70], superabsorbent polymer-containing products (commonly found in nappies and sanitary towels) [71], improvised explosive devices [72], rifle magazines [73] and bullet cartridges [74][75][76][77][78]. Further, Gray et al [79] demonstrated that STR DNA profiles can be generated from human blood found in Anopheles mosquitoes, from one or multiple individuals, and that the quality of the profiles declined as the duration between mosquito blood meal and sample collection increased.…”
Section: Samplingmentioning
confidence: 99%
“…A terrorist attack followed by an explosion of IEDs can leave invisible traces of detonated explosives [28,29]. These traces exist because some parts of explosives may not react to combustion.…”
Section: Introductionmentioning
confidence: 99%